2009
DOI: 10.1097/jcp.0b013e3181bf613e
|View full text |Cite
|
Sign up to set email alerts
|

Improved Body Weight and Metabolic Outcomes in Overweight or Obese Psychiatric Patients Switched to Amisulpride From Other Atypical Antipsychotics

Abstract: Switching to a different second-generation antipsychotic (SGA) with a lower risk of weight gain is recommended for overweight or obese psychiatric patients undergoing SGA treatment. However, there have been no complete reports regarding the long-term metabolic effects of switching to amisulpride. In this open-label 1-year study, we investigated the effects on body weight and other metabolic profiles when psychiatric patients treated with another SGA were switched to amisulpride treatment. Forty-six schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…According to a previous meta-analysis of head-to-head comparisons of the metabolic side effects of atypical antipsychotics,37 olanzapine produces more weight gain and a greater increase in cholesterol and glucose than other atypical antipsychotics. However, aripiprazole among atypical antipsychotics has shown a relatively lower risk of MetS than other antipsychotics 383940. In line with these reports, the prevalence of MetS was highest in our clozapine group and the patients who had been prescribed aripiprazole had the second lowest prevalence of MetS.…”
Section: Discussionsupporting
confidence: 87%
“…According to a previous meta-analysis of head-to-head comparisons of the metabolic side effects of atypical antipsychotics,37 olanzapine produces more weight gain and a greater increase in cholesterol and glucose than other atypical antipsychotics. However, aripiprazole among atypical antipsychotics has shown a relatively lower risk of MetS than other antipsychotics 383940. In line with these reports, the prevalence of MetS was highest in our clozapine group and the patients who had been prescribed aripiprazole had the second lowest prevalence of MetS.…”
Section: Discussionsupporting
confidence: 87%
“…While some have just followed up patients on the same antipsychotics that they have been receiving at baseline,[106107111113] a few have reported the change in prevalence rate after change in antipsychotic. [112114116117] Some of the studies have evaluated the effect of various antipsychotics by randomizing the study sample to different antipsychotic medications. [109110118] While most of the studies have included adult patients, two studies longitudinally evaluated MetS in pediatric population.…”
Section: Prevalence Of Metabolic Syndrome In Schizophreniamentioning
confidence: 99%
“…Likewise, a number of short-term [92-96] and long-term [97-99] studies have shown a significant decrease in weight and other cardiometabolic risk factors in patients switched to a lower weight and metabolic risk antipsychotic. For example, in a one-year study [99], patients switching from a first-generation antipsychotic to ziprasidone did not show any relevant change in weight or triglyceride levels.…”
Section: Strategies To Reduce Antipsychotic Associated Weight Gain Anmentioning
confidence: 99%